Improvement of Power Quality using Fuzzy Logic Controller In Grid Connected Photovoltaic Cell Using UPQC - K.Ramalingeswara Rao; K.S. Srikanth (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
In this paper, the design of combined operation of UPQC and PV-ARRAY is designed. The proposed system is composed of series and shunt inverters connected back to back by a dc-link to which pv-array is connected. This system is able to compensate voltage and current related problems both in inter-connected mode and islanding mode by injecting active power to grid. The fundamental aspect is that the power electronic devices (PE) and sensitive equipments (SE) are normally designed to work in non-polluted power system, so they would suffer from malfunctions when supply voltage is not pure sinusoidal. Thus this proposed operating strategy with flexible operation mode improves the power quality of the grid system combining photovoltaic array with a control of unified power quality conditioner. Pulse Width Modulation (PWM) is used in both three phase four leg inverters. A Proportional Integral (PI) and Fuzzy Logic Controllers are used for power quality improvement by reducing the distortions in the output power. The simulated results were compared among the two controller’s strategies With pi controller and fuzzy logic controller.DOI: http://dx.doi.org/10.11591/ijpeds.v5i1.6184